Efektivitas Pembelajaran Problem Solving untuk Meningkatkan Berpikir Kritis pada Hasil Belajar Ekonomi - Agustin, Imelda Dwi (Jurnal Pendidikan Ekonomi Undiksha, 2025)
This study aims to analyze the effectiveness of the problem-solving-based learning method in improving critical thinking skills and student learning outcomes in Economics subjects. The research employed a quantitative descriptive approach with a survey design, involving 50 students of the Economics Education Program at Universitas Negeri Surabaya (UNESA) selected through purposive sampling. Data were collected using questionnaires and interviews, then analyzed using descriptive statistics along with validity and reliability tests. The results revealed that problem-solving-based learning is effective in enhancing critical thinking skills, as indicated by significant correlations across all variables and high consistency with Cronbach's Alpha values above 0.7. This method encourages students to actively analyze problems, seek solutions, and apply economic concepts to real-life contexts. These findings support the use of problem-solving-based learning as an innovative approach to improve the quality of Economics education in the 21st-century education era.